Admission serum phosphate levels and the risk of respiratory failure. Issue 4 (18th December 2019) - Thongprayoon, Charat; Cheungpasitporn, Wisit; Chewcharat, Api; Mao, Michael A.; Thirunavukkarasu, Sorkko; Kashani, Kianoush B.
Abstract: Background: The objective of this study was to evaluate the relationship between admission serum phosphate and in‐hospital respiratory failure requiring mechanical ventilation in hospitalised patients. Methods: We analysed a cohort of all adult patients admitted at a tertiary referral hospital between the year 2009 and 2013. We included patients who had available serum phosphate and were not on mechanical ventilation within 24 hours of hospital admission. We stratified admission serum phosphate based on its distribution into 6 groups: ≤2.4, 2.5‐3.0, 3.1‐3.6, 3.7‐4.2, 4.3‐4.8 and ≥4.9 mg/dL. We performed multivariable logistic regression analysis to assess the odds ratio of in‐hospital respiratory failure requiring mechanical ventilation based on admission serum phosphate, using phosphate level of 3.1‐3.6 as the reference group. Results: This study enrolled a total of 37 728 hospitalised patients, with a mean admission serum phosphate of 3.8 ± 1.1 mg/dL. Of these patients, 2792 (7.4%) developed respiratory failure requiring mechanical ventilation during hospitalisation. Increased incidence of respiratory failure requiring mechanical ventilation was observed in both decreased and increased admission serum phosphate, assuming the J‐shaped curve. In adjusted analysis, admission serum phosphate of ≤2.4 and 2.5‐3.0 mg/dL was significantly associated with increased risk of respiratory failure requiring mechanical ventilation with odds ratio (OR) of 1.18 (95% confidence interval [CI] 1.01‐1.40) and 1.19 (95% CI 1.04‐1.35), respectively. Similarly, admission serum phosphate of 4.3 to 4.8 and ≥4.9 mg/dL was significantly associated with increased risk of respiratory failure requiring mechanical ventilation with OR of 1.19 (95% CI 1.05‐1.36) and 1.58 (95% CI 1.37‐1.82), respectively. Conclusion: Our study revealed the J‐shaped association between serum phosphate level at admission and risk of respiratory failure requiring mechanical ventilation in unselected hospitalised patients.